PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA INDIVIDU PEGAWAI DISTRO DI KOTA BANDUNG - Sheilla Puteri Suhud; Abdul Rohman (Diponegoro Journal of Accounting, 2015)
This study discuss about the Effect of Accounting Information Systems Implementation on individual performance, as well as how much Effect of Accounting Information System Implementation of the Individual Performance. The independent variable used is the utilization of Accounting Information Systems, Quality of Accounting Information Systems, Information Systems Security, and Accounting Information Systems Supporting Facilities which part of user satisfaction.The samples in this study were taken using purposive sampling method of data collection, with the criterias are computer ownership and the respondents are direct users of information systems. This study uses distribution outlet’s employees with a population of 35 people. While the sample taken is 32 respondents. The data were obtained then analyzed using descriptive statistics technical analysis, data quality test, classic assumption test and multiple linear regression analysis. The results of this study indicate that utilization of accounting information systems, the quality of accounting information systems, and supporting facilities of accounting information systems has a significantly positif effect on the individual performance. While the accounting information system security is not significantly effect the individual performance.